"One Belt, One Road": China's New Global Strategy. Issue 2 (1st January 2016) - Aoyama, Rumi
Abstract: The "One Belt, One Road" (OBOR) initiative has been a topic of hot debate among Sinologists and pundits in recent years. What is the nature of this foreign policy and how is it implemented under the Xi Jinping administration? By examining China's OBOR initiative, this article argues that OBOR is not only a regional policy but a grand global strategy for achieving the "Chinese Dream". While there is little chance that China will be able to create a large area of influence around the world, the potential impact on global politics cannot be overlooked.